The complete book of offensive basketball drills game-changing drills from around the world - Gandolfi, Giorgo editor-in-chief (McGraw-Hill, 2010)
The complete book of offensive basketball drills helps you take your team to the next level with the most effective offensive drills from the world's best coaches. Run practice sessions that can produce dominant players using these elite instructional workouts taken from around the globe. You'll bring a fresh perspective on the game to your players, all while teaching solid fundamentals, improving offensive performance, and driving up the score with teams at any level